Simulation modeling of parts stamping line with four presses - S. V. Lukyanets; S. V. Snisarenko; M. A. Lishay (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The algorithm of the imitation simulation of the automated four-press line of details' stamping is developed. The computer experiment is executed. Characteristics of the line depending on the size of details' party are received. Recommendations how to improve the efficiency of production and workers' safety are given.